The state of the knowledge-based economy in the Arab world: cases of Qatar and Lebanon. Issue 2 (20th July 2020) - Ben Hassen, Tarek
Abstract : Purpose: The purpose of this paper is to examine the current state of the knowledge-based economy in two distinctive case studies in the Arab World: Qatar and Lebanon. Based on five aspects of the knowledge-based economy namely: ICT, human capital and education; innovation, entrepreneurship, and economic and institutional regime, we provide a careful view of the obstacles and challenges that Qatar and Lebanon are facing and how this is hindering their transformation to a knowledge-based economy. Design/methodology/approach: The methodology of this research is based on a literature review and information collected through semi-structured interviews with the different stakeholders of the knowledge-based economy in Qatar and Lebanon. Findings: The research reveals that numerous factors shape the knowledge-based economy in Qatar and Lebanon. In Qatar, the main strength of the knowledge-based economy is the determination of the Qatari government to diversify the economy and the main weaknesses are the shortage of qualified human resources, the fear of failure and the low performance of the innovation system. In Lebanon, the knowledge-based economy is driven by the education system and the entrepreneurship culture, nevertheless the political instability of the country and the weak ICT infrastructure impede its development. Originality/value: These findings contribute to the clarification and critical analysis of the current state of the knowledge-based economy in Qatar and Lebanon, which would have several policy implications.